Traffic Guidance for Inclement Weather using GPS Navigation System - Sandeep, G.; Shanmathi, S.; Keerthana, K.Sahiti; M.E, Ms.S. Suchithra (IJRDO -Journal of Computer Science Engineering, 2017)
This work mainly focuses on the concept of guiding the Traffic during inclement weather conditions. Inclementweather effects the movement of vehicles leading to Traffic Congestion. Due to the inclement weather changes, roads getblocked which leads to delay in the movement of vehicles. To avoid these issues, GPS Navigation System is used where in,the user is guided to use an alternative path to their destination. GPS Navigation System , provides the alternative route tothe user based on their source and destination points. Alternate path is indicated through intermediate point locationsbetween the source and destination of the user. Intermediate locations are also checked to be unblocked and traffic free.Navigation in this GPS Navigation System is done mainly with help of Google Maps API.